Historiografi Korupsi di Indonesia: Resensi Buku Korupsi dalam Silang Sejarah Indonesia - Miftakhuddin Miftakhuddin (Universitas Islam Negeri Alauddin Makassar, 2019)
This review aims to describe the contents of the book, analyze how the book reaches its objectives, and how the author's perspective in presenting his arguments and ideas. The review was conducted by using the report method proposed by Bond (1964). Overall, this book has three weaknesses. Firstly, Carey's writings were not well-translated, so it might complicate nonscholar readers. Secondly, discussion in the first two chapters strays from the topic of